Expert system for mould base / Mohd Husmadi Husain, Mohd Masri Mohd Mustaffa and Nurliza Md Desa - Husain, Mohd Husmadi; Mohd Mustaffa, Mohd Masri; Md Desa, Nurliza (Faculty of Mechanical Engineering, 1997)
The final project report is trying to explain and clarify some of the aspects and procedures of designing and fabrication of a plastic mould. A typical product also has been design for the purpose of this project. The mould has been designed according to the standard design methodology and standard mould base is used for the purpose of the fabrication. This design has been proved workable when it was successfully machined assembled and the mould was used to obtain the product. In addition, this mould has been injected on the plastic ejection moulding and found successfully. Apart from that, the design of the product, assembly drawing and detail of part drawing are also enclosed. Also we find, it is useful to show the end result of the project that we have been working on.